Kinanthropometry and dietary habits of non-professional rugby players - Holway, Francis E.; Campa, Francesco; Petri, Cristian; Spena, Luciano R.; Szydlowski, Natalia Y. (Frontiers in Sports and Active Living, 2024)
Introduction Evaluating the body composition and dietary habits of non-professional athletes can help identify areas for improvement to enhance sports performance. The present study aimed to describe the anthropometric and body composition features, as well as the dietary habits, of non-professional rugby players in Argentina. Methods Fifty-seven rugby players from a Group III Club of the Unión de Rugby de Buenos Aires (URBA) were assessed using extensive anthropometric measurements according to the International Society for the Advancement of Kinanthropometry (ISAK) protocol. Reference data from professional rugby players in Group I clubs were used as a control for body composition comparisons. Dietary intake was evaluated using the 24-h recall method, and nutrient analysis was performed with SARA software. Results Non-professional rugby players were shorter (Forwards: 175.9 vs. 181.5 cm; Backs: 172.5 vs. 175.7 cm), had higher body fat percentages (Forwards: 16.4 vs. 12.3%; Backs: 11.0 vs. 9.3%), and were less muscular (Forwards: 46.0 vs. 48.8%; Backs: 48.4 vs. 50.2%) compared to professional rugby players. The average dietary intake was 3,363 Kcal, with protein and carbohydrate intakes of 1.4 g kg−1 day−1 and 4.1 g kg−1 day−1, respectively, and 35% of energy intake from fat. Backs reported a higher caloric intake than forwards (3,682 vs. 2,827 Kcal). There was a high prevalence of insufficient intake of calcium (58%), vitamin A (49%), and vitamin C (65%), the latter two corresponding with a low intake of fruits and vegetables (6% of total energy intake). Meal pattern analysis showed that 46% of total energy was ingested at dinner. Conclusions The body composition of non-professional rugby players from low-income clubs could be improved to enhance rugby performance, as compared to players in more competitive tiers. Economic constraints might contribute to a sub-optimal nutritional profile, potentially affecting body composition and on-field performance negatively. Recommendations to improve dietary intake should be made considering the budget constraints of these players.